Necesidad de derogar el art. 254 del código civil el cual vulnera el derecho de la mujer a solicitar reconocimiento judicial de paternidad para su hijo - Roblez Paladines, Robinson Saúl (2015)
Article 253 of the Ecuadorian Civil Code states that the judicial recognition of paternity may be declared if there was cases of abduction, rape, detention or personal kidnapping arbitrarily mother, or in the case of seduction done maliciously, or that they have lived in notorious concubinage; however it the following article this is the 254 states that the court must reject the claim based on these cases if it is proved that during the legal period of conception the mother was notorious misconduct, or had relations of this nature do Presumably the sexual intercourse with another individual. It is then necessary to analyze this article emphasize that it constitutes cruel and formal discrimination against women in general, since while there is talk of a notorious misconduct or that it maintains sexual relations with other individuals are circumstances that should not influence in fact determine the identity of a person, and through a physical exam paternity grant to an individual and so did not even violate the rights of children to their own identity. The characterization of the human person with all its features, is imposed by the genetic material from zygote remains evolve naturally as you become forms of embryo, fetus, child, adolescent and adult. Thus this right is important, because it allows to establish the provenance of children from parents, because it is such a natural and undeniable fact that nobody can ignore and is the most important relationship in life, its effect is manifested not only in the family but in the social structure, that is the right to know who his father and mother; and this undoubtedly contributes to the identification of a person. The right to identity elements are: fatherhood, motherhood, physical and moral character, profession, residence etc. I think and believe that at the present time of Ecuadorian society, can no longer afford the laws violate the rights of the people and serve rather to be a barrier to their rights, the fact determine misconduct of a woman It should not be an occasion to reject a claim or go to the administrators of justice to enforce their rights and also the rights of their children. For the above noted background I consider that Article 254 of the Civil Code be repealed from our Ecuadorian civil law.